A hierarchical emulsion system stabilized by soyasaponin emulsion droplets. Issue 21 (28th September 2021) - Zhao, Guo-Xiu; Zhu, Li-Jie; Li, He; Liu, Xiu-Ying; Yang, Li-Na; Wang, Sheng-Nan; Liu, He; Ma, Tao
Abstract : Oil/water (O/W) emulsion droplets coated with soyasaponin (Ssa) were used as emulsifiers to prepare emulsions with hierarchical configurations (2.82 μm). Abstract : Oil/water (O/W) emulsion droplets coated with soyasaponin (Ssa) were used as emulsifiers to prepare emulsions with hierarchical configurations (2.82 μm). Ssa is a natural triterpenoid with amphiphilic properties and an excellent emulsifying activity. Stable O/W emulsions were prepared and characterized using an ultrasonic method at a Ssa concentration of 2.5 wt%. The resultant hierarchical emulsions were further prepared using O/W droplets as emulsifiers. It was observed that the stability of the hierarchical emulsions changed with alterations to the ratio of O/W droplets to the oil phase. As the number of droplets increased, the more the surface area of the hierarchical emulsion was covered. Additional observations included a decreased particle size, increased negative charge and viscoelastic behavior, and enhanced emulsion stability. The emulsion was most stable when the O/W droplet addition was 29%. The addition of O/W droplets continued to increase, and there was an imbalance in the ratio of O/W droplets to the oil phase; the excess O/W droplets induced instability in the emulsion, resulting in a degradation of the emulsion quality. We monitored hierarchical emulsions with different concentrations of emulsifiers for 30 days, and the results indicated that hierarchical emulsions could meet the demand for long-term storage. This provides a new theoretical basis for the construction and application of complex emulsion systems.